Plant Milk: A Suitable Dairy Milk Substitute for Human Health - Siddhant Parashar; Seema Sonkar; Shalini Suman (Contemporary Research and Perspectives in Biological Science Vol. 2, 2024)
Worldwide, the market for dairy milk substitutes is expanding quickly in the group of functional and specialty beverages under the newer food product development umbrella. These days, customers choose cow milk substitutes because of lactose intolerance, allergies to cow milk, concerns about calories, the incidence of hypercholesterolemia, and a growing desire for vegan diets. An increasing number of people are turning to plant-based milk substitutes as an affordable option for those in developing nations with low incomes and in areas with a scarcity of cow’s milk. While the majority of these milk substitutes don’t have the same nutritional profile as real milk from cows, their functional ingredients and health-promoting qualities draw in consumers who are concerned about their health. The broad acceptance of legume-based milk substitutes is significantly hampered by their sensory appeal. Research is being done on cutting-edge non-thermal processing techniques like pulsed electric field processing, ultra-high pressure homogenization, and ultra-high temperature treatment to address issues with the final product’s sensory acceptability, emulsion stability, shelf life, and nutritional completeness. In the upcoming years, focused research efforts in the functional beverage sector will be needed to create new, customized products that are both tasty and nutritionally sound.